Isolation and molecular characterization of Enterobacter species ENKS2 and its phosphate solubilisation from rhizospheric soil - Krishnamoorthy, Santhanalakshmi; Ekambaram, Natarajan (International Journal of Scientific Research in Biological Sciences, 2018)
In this present study, the potential of a phosphate solubilising bacterium (PSB) was isolated from rhizosphere soil. The phosphate solubilisation was grown in Pikovskaya’s agar medium and the isolate was purified in AT salt minimal medium and further it was cultured in NBRIP liquid media for characterization, identification processes. Based on the morphological, biochemical characterization and 16S rRNA gene sequencing the phosphate solubilising bacterium was identified as Enterobacter species ENKS2. The maximum phosphate solubilisation was in 96h at pH 7.3 in NBRIP liquid media. The Enterobacter species ENKS2 optimized phosphate solubilisation was at pH 7 (281µg/cfuX106), temperature at 30°C (268µg/cfuX106) at pH 6.8, salt conditions was 0.5% (169µg/cfuX106) at pH 7.1, carbon source xylose (213µg/cfuX106) at pH 6.3 and nitrogen source Pottassium nitrate (212µg/cfuX106) at pH 6.1. The different time intervals were followed to maximum phosphate solubilisation in 96h (531µg/cfuX106) at pH 5.8. Hence, this study was useful to develop the biofertilizer for improves the soil, plant growth and reduce the chemical fertilizer usages.